Re-desain Brand Identity UD KS PRO Sebagai UMKM di Bidang Otomotif - M Syaifullah Islamudin; Aditya Rahman Yani; Widyasari (Yayasan Sagita Akademia Maju, 2025)
MSMEs play a vital role in Indonesia's economy, yet many still lack awareness of the importance of visual identity in boosting competitiveness. This study discusses the re-design of the brand identity of UD KS PRO, a trading business in the automotive sector, to strengthen brand image and increase brand awareness. The research applies a mixed-methods approach, collecting data through interviews, observation, and questionnaires. Data were analyzed using the TWOS matrix to formulate rebranding strategies. The results indicate that UD KS PRO’s previous visual identity was inconsistent and failed to effectively represent the company's business field. By developing a new logo, typography, and color palette that are more professional and relevant, UD KS PRO is expected to improve consumer perception, expand its market reach, and enhance customer trust. This study highlights the importance of research-based rebranding as a strategic step for MSMEs to adapt in the digital era and ensure sustainable business growth.